KCNQ2 Encephalopathy and Neonatal Seizures - J Gordon Millichap (Pediatric Neurology Briefs)
Researchers from centers in Belgium and Australia analyzed 80 patients with unexplained neonatal or early infantile seizures and associated psychomotor retardation for KCNQ2 mutations.